Self-Determination in Marriage: Actor and Partner Effects of Spousal Autonomy on Relationship Maintenance Behaviors. (2nd September 2022) - Goodboy, Alan K.; Myers, Scott A.; Goldman, Zachary W.; Borzea, Dana
Abstract : Guided by self-determination theory, this study examined the dyadic effects of marital autonomy on relationship maintenance behaviors. Heterosexual married couples (N = 324 dyads) completed questionnaires assessing their need fulfillment of autonomy in marriage along with their enactment of relationship maintenance behaviors. Using multilevel modeling, actor-partner interdependence models were estimated to determine dyadic effects for husbands' and wives' autonomy on their own and their partners' use of positivity, openness, assurances, social networks, and shared tasks. Parameter estimates revealed that husbands' and wives' autonomy produced equivalent positive actor and partner effects for the positivity, assurances, social networks, and shared tasks maintenance behaviors, and a positive actor effect for the openness maintenance behavior. These dyadic findings support the idea of mutuality of autonomy support in marriage.